Cardiac MRI of acute coronary syndrome. (May 2013) - Khan, Shamruz Akarem; Williamson, Eric E; Foley, Thomas A; Cullen, Ethany L; Young, Phillip M; Araoz, Philip A
Acute coronary syndrome (ACS) is a major cause of morbidity and mortality worldwide. New serological biomarkers, such as troponins, have improved the diagnosis of ACS; however, the diagnosis of ACS can still be difficult as there is marked heterogeneity in its presentation and significant overlap with other disorders presenting with chest pain. Evidence is accumulating that cardiac MRI provides information that can aid the detection and differential diagnosis of ACS, guide clinical decision-making and improve risk-stratification after an event. In this review, we present the relevant cardiac MRI techniques that can be used to detect ACS accurately, provide differential diagnosis, identify the sequelae of ACS, and determine prognostication after ACS.